PECULIARITIES OF PRODUCTION AND TECHNICAL PRODUCTION AND TECHNICAL EXPLOITATION OF THE USE OF TECHNOLOGY IN THE AGROTECHSERVICE ENTERPRISE - YUSIFOV SAMAD, NURADDIN (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The purpose of the article is to improve the production and technical exploitation of the machine-tractor fleet and the efficient use of machinery in the service area with the use of application of resuscitation techniques. The methodology and methods used are the theoretical and methodological basis of the research work of our country and foreign scientists on the technical maintenance of agricultural production, the organization and effective functioning of the institutions implementing it. Here a number of methods of analysis of mass service theory and graph theory are used. The main scientific novelty of the results is the use of integrated indicators to mechanize technological processes in the context of existing structural features of agricultural production, to increase the operating level of the machine-tractor fleet. The production and technical exploitation depends on the level of technical maintenance of the process. The results of the research are joint review of “production and technical exploitation” and resuscitation techniques in ensuring the mechanization of technological processes in the context of existing structural features of agricultural production; the use of a comprehensive indicator for assessing the operational level of the machine-tractor fleet; development of the model of production and technical exploitation of the fleet based on four groups that characterize the usefulness of organizational, technical and technological measures, as well as methods of increasing the level of technical service of various economic entities to ensure the quality of the machine-tractor fleet operation: – Existing forms of technical and technological classification of mechanization of production processes in agriculture and increasing the intensity of use of machines in established engineering service facilities; – Improvement of production and technical exploitation of machine-tractor fleet of service enterprises operating in economic climatic conditions and improvement of use of machines with application of resuscitation techniques; – Ensure that labor costs and maintenance and repair in the manufacturing process are lower than the cost of 15 manat per conventional ha etalon;– Ensure the performance of the whole complex of mechanized work with the effective use of the machine-tractor fleet.
Keywords: Large company farms; agroservice enterprise; production-technical exploitation; optimal method; means of supply; labor capacity; complex indicators; generalized factors; production resources; conventional ha etalon